1) ((m-(2*sqrt(mn))+n)/(m-n)) 2) ((a+3*sqrt(a))/(a-9) 3) a/(a-1)-(sqrt(a))/(sqrt(a)+1)

0 голосов
49 просмотров

1) ((m-(2*sqrt(mn))+n)/(m-n))
2) ((a+3*sqrt(a))/(a-9)
3) a/(a-1)-(sqrt(a))/(sqrt(a)+1)


Математика (36 баллов) | 49 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

1)
\frac{m - 2 \sqrt{mn} + n }{m - n} = \frac{ {( \sqrt{m} - \sqrt{n} )}^{2} }{( \sqrt{m} - \sqrt{n} )( \sqrt{m} + \sqrt{n}) } = \frac{ \sqrt{m} - \sqrt{n} }{ \sqrt{m} + \sqrt{n} }
2)
\frac{a + 3 \sqrt{a} }{a - 9} = \frac{ \sqrt{a}( \sqrt{a} + 3)}{( \sqrt{a} - 3)( \sqrt{a} + 3)} = \frac{ \sqrt{a} }{ \sqrt{a} - 3}
3)
\frac{a}{a - 1} - \frac{ \sqrt{a} }{ \sqrt{a} + 1 } = \frac{a}{( \sqrt{a} - 1)( \sqrt{a} + 1) } - \frac{ \sqrt{a}( \sqrt{a} - 1) }{( \sqrt{a} + 1)( \sqrt{a} - 1) } = \frac{a - a + \sqrt{a} }{a - 1} = \frac{ \sqrt{a} }{a - 1}

(41.5k баллов)